Dios en los confines: La cuestión de Dios en una cultura postcristiana - Cordovilla Pérez, Ángel (Estudios eclesiásticos, 2022)
In this article I intend to summarize some of the most significant issues that our current culture raises around the question of God. Having clarified the adjective post-Christian in reference to our culture or what we understand by post-Christianity (1), I have summarized these borderline questions (edges) around the new debate on the existence of God between atheism and theism (2); the question of his reality as a personal being or as an absolute incomprehensible mystery, as defended by radical apophatic currents (3); the question of the possibility of his action and presence in the world in a world understood from a scientific mentality (4); and, finally, the question of his monotheistic confession and the current praise of polytheism (5). From this background of problems, we are committed to deepen in the incomprehensible character of the mystery of God that is always beyond our horizon, but this mystery is always Trinitarian, as it has revealed itself in history (6).